Associations of Blood Pressure With Common Factors Among Left-Behind Farmers in Rural China. Issue 2 (January 2015) - Shen, Xingrong; Li, Kaichun; Chen, Penglai; Feng, Rui; Liang, Han; Tong, Guixian; Chen, Jing; Chai, Jing; Shi, Yong; Xie, Shaoyu; Wang, Debin; Angeli., Fabio
<x xml:space="preserve">Abstract</x> Abstract The whole range of blood pressure (BP) has important implications. Yet, published studies focus primarily on hypertension and hypotension, the two extremes of BP continuum. This study aims at exploring quantile-specific associations of BP with common factors. The study used cross-sectional survey, collected information about gender, age, education, body mass index (BMI), alcohol intake, diet risk behavior, life event index, physical activity, fasting capillary glucose (FCG), and systolic/diastolic blood pressure (SBP/DBP) and pulse pressure (PP) from farmers living in 18 villages from rural Anhui, China, and performed descriptive and multivariate and quantile regression (QR) analysis of associations of SBP, DBP, or PP with the 9 factors surveyed. A total of 4040 (86.3%) eligible farmers completed the survey. Average hypertension prevalence rate and SBP, DBP, and PP values estimated 43.20 ± 0.50% and 141.37 ± 21.98, 87.76 ± 12.23, and 53.63 ± 15.72 mm Hg, respectively. Multivariate regression analysis revealed that all the 9 factors were significantly (P < 0.05) associated with one or more of SBP, DBP, and PP. QR coefficients of SBP, DBP, or PP with different factors demonstrated divergent patterns and age, BMI, FCG, and life event index showed substantial trends along the quantile axis. Hypertension prevalence rate was high among the farmers. QR modeling provided more detailed view on associations of SBP, DBP, or PP with different factors and uncovered apparent quantile-related patterns for part of the factors. Both the population group studied and the trends in QR coefficients identified merit specific attention.